Legislative safeguards for the protection of a minor’s real estate property in Algerian law - Menagguer, Nafissa; Hamaiti, Sabah (The International tax journal, 2025)
Most modern legal systems, including Algerian legislation, provide a comprehensive set of legal safeguards designed to protect a minor’s real estate assets. These protections focus primarily on regulating who is authorized to manage such assets in order to prevent their loss or misuse. The financial protection of a minor involves appointing a legal guardian or custodian with the authority to manage the minor’s property and bear the legal consequences of such management. Furthermore, Algerian law requires judicial oversight in specific transactions that involve the minor’s property. In such cases, the guardian or custodian must first obtain the court’s authorization before proceeding. This reflects the principle that decisions made on behalf of a minor are not left to full discretion but must be conducted under judicial supervision. The law thereby imposes restrictions to prevent abuse and to ensure that any act concerning a minor’s real estate serves their best interest.